Genealogi Jaringan Intelektual Ekonomi Islam: Interkoneksi Ulama, Institusi, dan Transformasi Pemikiran Era Klasik hingga Kontemporer - Kumaidi Kumaidi; Syukri Iska; Fauzani Fauzani; Jasri Waldi; Fitri Yenti (Al-Buhuts, 2026)
This article is a conceptual paper based on historical-genealogical literature review that aims to build an intellectual genealogy model of Islamic economics. Previous studies have tended to address figures, institutions, or research trends separately (see e.g. single-figure studies, bibliometric studies, or historical studies of educational institutions), so there is no framework that brings these three elements together in a single analytical model. Based on a critical synthesis of 15 selected sources through the PRISMA protocol, this study offers a major contribution in the form of a triadic layered genealogy model that connects (1) the scholarly sanad of three influential classical scholars  Al-Ghazali, Ibn Khaldun, and Ibn Taymiyah  as a network that complements each other despite different emphasis (individual ethics, social dynamics, and state regulation); (2) Islamic educational institutions, from halaqah and madrassas to modern Islamic universities, as the node of transmission that most determines the sustainability of ideas across generations; and (3) adaptive transformation mechanisms through instruments such as waqf and shariah governance, which on the other hand are vulnerable to being distorted by neoliberal financialisation and epistemic hegemony, including halal-washing practices. Given that the scope of the study is limited to 15 selected literature, these findings are intended as an initial conceptual model, rather than a comprehensive generalization across eras and regions. This model is expected to be a foothold for the development of a curriculum based on intellectual genealogy and the strengthening of epistemological criticism of the commercialization of contemporary Islamic economics.